PENGEMBANGAN GAME EDUKASI CERMAT BERBASIS ANDROID UNTUK MENINGKATKAN KETERAMPILAN PROBLEM SOLVING SISWA SMA PADA MATERI BARISAN DAN DERET GEOMETRI - Fahlevi, Reza (IKIP Siliwangi, 2021)
This research aims to develop android-based interactive learning media improves the problem solving skills of high school students in understanding the concept of geometric sequences and series. This type of research is development research with qualitative approach supported by quantitative data. Methods used research and development (R&D) that adapt ADDIE model. This CERMAT learning media innovation work was created using Adobe Flash Professional CC 2015 with android-based. This type of game is categorized as RPG (Role Playing Game). The subject of this study was a grade XI student at high schools in West Bandung Regency with a sample of 22 students. The data collection technique used is 1.) problem solving skill test in the form of pretest-posttest description of 6 questions of concept geometric sequences and series; 2.) student response questionnaire as many as 20 statements; 3.) interview results and media validation. Data analysis techniques using Normalized Gain test (N-gain). The results of the data analysis show that the feasibility level of educational games CERMAT amounted to 85,49% and N-gain test results of 0,836 with classical completion of 100% and average student score of 90,74. This shows that educational game media CERMAT is feasible and can improve problem solving skills.